LA REVOLUCIÓN 4.0 Y LOS RETOS AMBIENTALES EN COLOMBIA UNA GUÍA PARA COMPRENDER SU RELACIÓN - Geraldine Barreto (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2022)
This document gives an account of a qualitative research of documentary analysis that, through three chapters, addressestheoretical, technical, historical, and legal references on the historical development of industrialization in Colombia andits relationship with the country’s environmental challenges. It is intended to be an access guide to understand thechallenges faced by Colombian companies in terms of economic growth, development and contribution to the environmentand the scope of the Sustainable Development Goals of the World Agenda. Basically, it is based on a work of collecting,analyzing and systematizing key information to recognize the path of the country in terms of industrialization and theresponsibility of companies in protecting the environment in the new context of Revolution 4.0, which implies theinnovation of behavioral processes, both industry and of people, individually and collectively.